Complaint management and redress mechanism: the effect of fragmented institutional approach in regulating consumer credit in Malaysia - Hassan, Rusni; Kassim, Salina; Hingun, Mohsin; Abu Bakar, Elistina; Ilias, Ibtisam @ Ilyana (2018)
Complaint management and redress mechanism constitute a cardinal element of financial consumer protection which should be provided by financial consumer protection regulator. This study explores the role of the Central Bank of Malaysia, Ministry of Domestic Trade, Co-operatives and Consumerism as well as Ministry of Urban Wellbeing, Housing and Local Government to ensure proper complaint management and redress mechanism in favour of financial consumers of a different segment of consumer credit. Applying doctrinal, qualitative and comparative research methodology, the study finds that as a result of fragmented approach in regulating consumer credit in Malaysia, these aspects are pursued with different priorities and enthusiasm by respective regulators. Thus, the benefit of protection varies from one class of financial consumers to another. To ensure consistency and efficient protection, the study proposes for the establishment of a single regulator, the approach adopted by Australia, a jurisdiction renowned with an established track record in financial consumer protection regime.